Prenatal exposure to polycyclic aromatic hydrocarbons and growth parameters - Sram, Radim J; Solansky, Ivo; Pastorkova, Anna; Veleminsky, Milos; Veleminsky, Milos; Honkova, Katerina; Barosova, Hana; Schmuczerova, Jana; Urbancova, Katerina; Dvorakova, Darina; Pulkrabova, Jana (Journal of applied biomedicine, 2024)
BACKGROUND AND OBJECTIVES: It has long been known that airborne polycyclic aromatic hydrocarbons (PAHs) can negatively affect pregnancy and birth outcomes, such as birth weight, fetal development, and placental growth factors. However, similar studies yield divergent results. Our goal was to estimate the amount of monohydroxylated PAH (OH-PAH) metabolites in the urine of pregnant women/mothers and their newborns in relation to birth outcomes, such as placenta weight, Apgar 5', and the growth parameters of children up to the age of two. METHODS: Two cohorts of children born in 2013 and 2014 during the summer and winter seasons in the Czech Republic in the cities Karviná (N = 144) and České Budějovice (N = 198), which differ significantly in the level of air pollution, were studied. PAH exposure was assessed by the concentration of benzo[a]pyrene (B[a]P) in the air and the concentration of 11 OH-PAH metabolites in the urine of newborns and mothers. Growth parameters and birth outcomes were obtained from medical questionnaires after birth and from pediatric questionnaires during the following 24 months of the child's life. RESULTS: Concentrations of B[a]P were significantly higher in Karviná (p < 0.001). OH-PAH metabolites were significantly higher in the mothers' as well as in the newborns' urine in Karviná and during the winter season. Neonatal length was shorter in newborns in Karviná (p < 0.001), but this difference evened out during the next 3 to 24 months. Compared to České Budějovice, newborns in Karviná showed significantly lower weight gain between birth and three months after delivery. The OH-PAH metabolites in mothers' or newborns' urine did not affect birth weight. The presence of seven OH-PAH (top 25% of values of concentrations higher than the median) metabolites in the newborns' urine is associated with decreased length of newborn. Nine OH-PAH metabolites decreased placenta weight, which was the most significant, while seven OH-PAH metabolites decreased Apgar 5'. CONCLUSION: We have shown a possible connection between higher concentration of OH-PAH metabolites in newborns' urine and decreased length, head circumference, placenta weight, and Apgar 5', but not birth weight.
Keywords: polycyklické aromatické uhlovodíky; novorozenec; Infant, Newborn; Birth weight; Pregnancy; Humans; zpožděný efekt prenatální expozice; Polycyclic aromatic hydrocarbons; dítě; Child; porodní hmotnost; Placenta; Female; Growth parameters; lidé; Polycyclic Aromatic Hydrocarbons; ženské pohlaví; Birth length; Birth Weight; Head circumference; těhotenství; Placenta weight; Monohydroxylated PAH metabolites; Prenatal Exposure Delayed Effects; matky; placenta; Mothers